ANALISIS BEBAN KERJA GUEST SERVICE AGENT DAN BELLDRIVER PADA FRONT OFFICE DEPARTMENT DI TJOKRO PEKANBARU HOTEL - Dhea Heryantika; Syofia Achnes (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2017)
This study aims to determine the ideal number of employees of Guest Service Agent and Belldriver based on workload borne by employees at Tjokro Pekanbaru Hotel.Research conducted by descriptive quantitative method to discuss the issues raised. In this research sample there are only 6 people using census method, with the use of data collection techniques research the way of observation, interview, and documentation. By using exponential smoothing technique, the discussion is about 2 exponents in human resource plan which consists of exponent workload in producing a product, as work load analysis and cycle time to finish a product and to find the right number of employees.In the results of the research that has been done, for the whole of the calculation of the ideal working time for Guest Service Agent requires the addition of 2 people, and the results of the calculation of the ideal work time Belldriver requires 2 people. The exactness of the amount that should be met by Tjokro Pekanbaru Hotel.Keywords : Workload, Guest Service Agent, Belldriver, Whole of Ideal Employees